Modeling and simulation of some cell dispersion problems by a nonparametric method - Christina Surulescu; Nicolae Surulescu (Mathematical Biosciences and Engineering)
Starting from the classical descriptions of cell motion we propose some ways to enhance the realism of modeling and to account for interesting features like allowing for a random switching between biased and unbiased motion or avoiding a set of obstacles.For this complex behavior of the cell population we propose new models and also provide a way to numerically assess the macroscopic densities of interest upon using a nonparametric estimation technique.Up to our knowledge, this is the only method able to numerically handle the entire complexity of such settings.